2013
DOI: 10.1111/jvh.12071
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diabetes mellitus in a population‐based cohort of persons with chronic hepatitis B virus infection

Abstract: To investigate the effect of hepatitis B virus (HBV) infection on the development of diabetes mellitus (DM), we compared DM incidence and characteristics of Alaska Native persons with and without HBV infection. From 1990 to 2010, there were 52 incident DM cases among 1309 persons with infection vs 4557 DM cases among 85 698 persons without infection (log-rank test, P = 0.20). Compared to infected persons without DM, those with DM were significantly older (57.0 vs 47.4 years, P < 0.001) and had higher body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 5 publications
5
50
0
Order By: Relevance
“…Among these 15 studies, 8 were cross-sectional studies, 5 were case-control studies and 2 were cohort studies. Six studies showed a significantly higher prevalence of DM in HBV-infected patients than in the controls (4-9), 7 studies lacked evidence of a significant association between DM and HBV infection (6,12-17) and 2 studies revealed a lower prevalence of DM in patients with HBV (10,11 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these 15 studies, 8 were cross-sectional studies, 5 were case-control studies and 2 were cohort studies. Six studies showed a significantly higher prevalence of DM in HBV-infected patients than in the controls (4-9), 7 studies lacked evidence of a significant association between DM and HBV infection (6,12-17) and 2 studies revealed a lower prevalence of DM in patients with HBV (10,11 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have identified an association between HBV infection and the prevalence of DM; however, the results of those studies were inconclusive. Certain studies have supported the increased risk of DM in HBV-infected patients when compared with non-HBV-infected controls (4)(5)(6)(7)(8)(9) and certain studies have had different results (10)(11)(12)(13)(14)(15)(16)(17). To the best of our knowledge, no meta-analysis has ever focused on assessing the association between HBV infection and the risk of DM.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reports the incidence rate of DM in Japanese patients with AIH to be 15.0% (28), which is similar to the present study. The risk factors of DM onset in patients with chronic liver disease are reported to be male sex, advanced age and the presence of cirrhosis (13,14,27,29). The present study revealed that advanced age, male sex and corticosteroid use were risk factors of DM (Table 3).…”
Section: Discussionmentioning
confidence: 66%
“…Diabetes mellitus also occasionally occurs in HBV-infected patients; previous studies indicate the prevalence rate of DM is 6.3-12% in HBV infection (13)(14)(15)18). However, a recent population-based cohort study suggested that HBV infection had no effect on DM development (27). Moreover, the prevalence of DM in alcoholic liver disease and NAFLD ranges from 7.4 to 19% (11,19) and 2.5 to 22.5% (11,20), respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies on patients with hepatitis have also shown significant differences between diabetic and nondiabetic individuals regarding the mean ALT level (18,21), mean age, cirrhosis (23), mean BMI, AST, ALT, HbA1c, cholesterol, and triglyceride (24). Another study on patients with HBV showed that diabetic patients had a significantly higher mean age (47.4 vs. 57 years) and BMI (28.4 vs. 34.5 kg/m 2 ), compared to nondiabetic individuals (25).…”
Section: Discussionmentioning
confidence: 99%